2015
DOI: 10.1242/jcs.174359
|View full text |Cite
|
Sign up to set email alerts
|

Sorting nexin 5 (SNX5) selectively regulates dorsal ruffle-mediated macropinocytosis in primary macrophages

Abstract: The regulation of macropinocytosis, a specialised endocytosis pathway, is important for immune cell function. However, it is not known whether the biogenesis of macropinosomes involves one or more distinct pathways. We previously identified sorting nexin 5 (SNX5) as a regulator of macropinocytosis in macrophages. Here, we show that bone-marrow-derived macrophages from SNX5-knockout mice had a 60-70% reduction in macropinocytic uptake of dextran or ovalbumin, whereas phagocytosis and retrograde transport from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…Cells were successfully transfected with siRNA sequences targeting PAK-1 and Cdc42 (Fig. 6A) to investigate the roles of these proteins on initially the uptake of dextran that represents in the absence of growth factor activation, a constitutive fluid phase probe 60,61 . Our previous studies indicated that PAK-1 was involved in the cellular uptake of cationic cell penetrating peptides that may be inducing a form of macropinocytosis for cell entry 34,62 .…”
Section: Extracellular Vesicle Uptake In Cells Depleted Of Proteins Rmentioning
confidence: 99%
“…Cells were successfully transfected with siRNA sequences targeting PAK-1 and Cdc42 (Fig. 6A) to investigate the roles of these proteins on initially the uptake of dextran that represents in the absence of growth factor activation, a constitutive fluid phase probe 60,61 . Our previous studies indicated that PAK-1 was involved in the cellular uptake of cationic cell penetrating peptides that may be inducing a form of macropinocytosis for cell entry 34,62 .…”
Section: Extracellular Vesicle Uptake In Cells Depleted Of Proteins Rmentioning
confidence: 99%
“…The pH dependence of FcRn binding to ligand defines the intracellular location where the interaction takes place. Albumin is internalised by fluid phase endocytosis, possibly by the efficient macropinocytosis pathway, a pathway highly active in endothelial cells, macrophages and dendritic cells (Lim and Gleeson, 2011;Lim et al, 2015). Cell surface receptors may also be involved in the endocytosis of the FcRn ligands, especially for IgG via Fcγ receptors on haematopoietic cells.…”
Section: Introductionmentioning
confidence: 99%
“…At the behest of EGFR activation, SNX5 is recruited to PI(3,4)P2‐enriched membranes on early macropinosomes and it is present on tubulating macropinosomes, where in both cases, the SNX5 BAR domain may contribute to membrane curvature 41 , 42 . Macrophages, but interestingly not immature dendritic cells, from SNX5 knockout mice have significantly reduced macropinocytosis and dorsal ruffling 51 …”
Section: Macropinocytosismentioning
confidence: 99%
“…41,42 Macrophages, but interestingly not immature dendritic cells, from SNX5 knockout mice have significantly reduced macropinocytosis and dorsal ruffling. 51 A diagnostic feature of macropinocytosis, used to distinguish this pathway from clathrin-mediated endocytosis, is its sensitivity to inhibitors of Na + /H + ion exchangers, such as amiloride. 52,53 Although the mode of action of amiloride is controversial, it remains a useful experimental tool for blocking macopinocytic uptake of markers or pathogens.…”
Section: Macropinocytosismentioning
confidence: 99%